Effect of surfactant choice and concentration on the dimensions and yield of liquid-phase-exfoliated nanosheets - Griffin, Aideen; Nisi, Katharina; Pepper, Joshua; Harvey, Andrew; Szydłowska, Beata Maria; Coleman, Jonathan N.; Backes, Claudia (Chemistry of materials, 2020)
Liquid-phase exfoliation has progressed in recent years to become a common method for production of 2D materials. During exfoliation, surfactants can be used to stabilize the nanosheets against reaggregation. Here, using WS2 as a model system, we explore the effect of varying surfactant type and concentration on the yield and dimensions of the exfoliated nanosheets. For ionic surfactants, the mass of nanosheets produced was widely constant for low surfactant concentrations but decreased sharply for surfactant concentrations above ∼10 mM, regardless of surfactant. Very similar surfactant-concentration dependence was observed for both nanosheet length and thickness. Contrary to previous reports, this data implies that the optimum surfactant concentration is not linked to the critical micelle concentration. In addition, we found that surfactant concentrations as low as 0.07 mM yielded stable nanosheet dispersions with zeta potentials above 40 mV. By decoupling the exfoliation and stabilization effects of the surfactant, we have shown that it is the (de)stabilization process, rather than the exfoliation process, which links nanosheet concentration, size, and thickness to surfactant concentration.